If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x + 1 = 29x + 44 Reorder the terms: 1 + 14x = 29x + 44 Reorder the terms: 1 + 14x = 44 + 29x Solving 1 + 14x = 44 + 29x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-29x' to each side of the equation. 1 + 14x + -29x = 44 + 29x + -29x Combine like terms: 14x + -29x = -15x 1 + -15x = 44 + 29x + -29x Combine like terms: 29x + -29x = 0 1 + -15x = 44 + 0 1 + -15x = 44 Add '-1' to each side of the equation. 1 + -1 + -15x = 44 + -1 Combine like terms: 1 + -1 = 0 0 + -15x = 44 + -1 -15x = 44 + -1 Combine like terms: 44 + -1 = 43 -15x = 43 Divide each side by '-15'. x = -2.866666667 Simplifying x = -2.866666667
| (2x+1)(x+4)=2(1-x)(5-x) | | 16e+6=8e-12 | | 4e+8=2e-15 | | (3x-8)(4x+9)= | | -6+4(11-5m)= | | 7p-1=5p+11 | | 3y-y-8y= | | 3x-7=7-4x | | 3x+4x+5x-2x=4x+5x+20 | | 9x-7=8x-1 | | 2x^3+9x^2+4x+6=0 | | 4x-3y+5x-2y= | | 2x^3-9x^2+4x+6=0 | | 8*10+10y=80 | | =2(3b+5)+4(2b-3) | | 4x^2+5k=(5k+1)x | | 13x-49=7x+29 | | =3(a+2b)-3b | | 2+cosx=0 | | 2+2cosx=0 | | x^2=18y^2-y^4 | | 8ab+12ab-12a= | | 7(h+1)=3+7h | | 3(g-1)=-2(2+g) | | 36x^2y^3+xy^2= | | =b(b+3)-2 | | =6(a+3)+2 | | =8a+2(5-b)-2a | | 6x^3+4x^2-14x+4=0 | | 125r^2-45= | | 3(2d+3)=12 | | 12r^2-75= |